2023
DOI: 10.3390/agronomy13010215
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of GATA Gene Family under Different Nitrogen Levels in Arachis hypogaea L.

Abstract: Nitrogen, one of the essential elements, is a key determinant for improving peanut growth and yield. GATA zinc finger transcription factors have been found to be involved inregulation of nitrogen metabolism. However, a systematic characterization of the GATA gene family and patterns of their expression under different nitrogen levels remains elusive. In this study, a total of 45 GATA genes distributed among 17 chromosomes were identified in the peanut genome and classified into three subfamilies Ⅰ, Ⅱ and Ⅲ wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
5
1
Order By: Relevance
“…Here, we identified 32 GATA TFs in potato grouped into four classes. While previous findings suggested variations in the number of GATA groups between dicots and monocots, our results did not align with this observation (Li, Deng, et al, 2023 ; Reyes et al, 2004 ). Several reports indicated that GATA in different plants, especially dicots, is likely to have groups between four and seven (Reyes et al, 2004 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we identified 32 GATA TFs in potato grouped into four classes. While previous findings suggested variations in the number of GATA groups between dicots and monocots, our results did not align with this observation (Li, Deng, et al, 2023 ; Reyes et al, 2004 ). Several reports indicated that GATA in different plants, especially dicots, is likely to have groups between four and seven (Reyes et al, 2004 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Phylogenetic analysis indicated that the GATA proteins from P. ginseng, A. thaliana, and O. sativa were classified into A, B, C, and D groups. This classification is consistent with the grouping of GATA proteins in Setaria italica [64], A. hypogaea L. [66], Populus alba [69], Sorghum bicolor [70], Zea mays L. [71], and Fagopyrum tataricum [72]. Specifically, subgroup A had the highest number of GATAs, and members within the same subgroups exhibited higher sequence similarity.…”
Section: Discussionsupporting
confidence: 83%
“…By increasing or decreasing the expression of related enzyme genes, these TFs participate in multiple biological processes, including environmental stress responses, plant development and growth, and saponin synthesis [59][60][61][62]. The GATA family has been extensively characterized in several plant species, encompassing A. thaliana [8], O. sativa [8], Zea mays L. [63], Setaria italica [64], Triticum aestivum L. [65], and Arachis hypogaea L. [66]. However, a genome-wide analysis of the GATA family genes in P. ginseng has not yet been conducted previously.…”
Section: Discussionmentioning
confidence: 99%
“…GATA transcription factors have been demonstrated to play an important role in plant salt tolerance [ 21 , 46 ], temperature stress [ 47 ], chlorophyll production [ 26 ], and hormone treatment [ 48 ]. Because of the importance of the GATA gene family in abiotic stress and plant growth and development, it has been studied in plants such as peanuts [ 49 ] and cucumbers [ 24 ], but genome-wide discovery of the PbGATA family gene has not been pursued. As a result, genome-wide characterization and expression investigation of the GATA gene family will aid in our understanding of the GATA gene’s function and involvement in P. bournei .…”
Section: Discussionmentioning
confidence: 99%
“…Variations in conserved motif and gene structure across GATA protein family members are key factors for functional variability [ 49 , 54 ]. A PbGATA motif study revealed that ZnF_GATA, a critical domain for identifying PbGATA genes, was strongly conserved in virtually all PbGATA genes ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%